The wages of women in England, 1260-1850 - Humphries, J; Weisdorf, J (University of Oxford, 2014)
This paper presents a wage series for unskilled English women workers from 1260 to 1850 and compares it with existing evidence for men. Our series cast light on long run trends in women's agency and wellbeing, revealing an intractable, indeed widening gap between women and men's remuneration in the centuries following the Black Death. This informs several debates: first whether or not "the golden age of the English peasantry" included women; and second whether or not industrialization provided women with greater opportunities. Our contributions to both debates have implications for analyses of growth and trends in wellbeing. If the rise in wages that followed the Black Death enticed female servants to delay marriage, it contributed to the formation of the European Marriage Pattern, a demographic regime which positioned England on a path to modern economic growth. If the industrial revolution provided women with improved economic options, their gains should be included in any overall assessment of trends in the standard of living distorts the overall evaluation of the gains from industrialization.